RETRACTED: Comparison of sucrose, expressed breast milk, and breast-feeding on the neonatal response to heel prick (Retracted Article. See vol 4, pg 415, 2003) - ÖZEK, EREN (CHURCHILL LIVINGSTONE, 2001)
Newborns endure many heel pricks and other uncomfortable procedures during their first hospital stay. The aim of this study was to investigate the effectiveness of breast-feeding in reducing pain in newborns undergoing heel prick tests. One hundred thirty healthy term infants requiring a heel prick blood sampling for the Guthrie test were studied. Infants were randomly allocated to 1 of the following treatment groups: group 1, 25% sucrose (n = 35); group 2, breast milk (n = 33); group 3, sterile water (n = 34); and group 4, breast-feeding (n = 28). The median values of crying and recovery time and percent change in heart rate at 1, 2, and 3 minutes were recorded. A behavioral pain scale was applied according to the infant body coding system. The median crying time was 36, 62, 52, and 51 seconds in groups 1, 2, 3, and 4, respectively (P = .002). Similarly, there was a significant overall difference among groups for the duration of recovery time (P = .006) and the percent change in heart rate at 1 (P = .03), 2 (P = .01), and 3 (P = .009) minutes favoring the sucrose group. But when we compared the groups, the significance remained for the sucrose versus breast milk (P = .007) and water (P = .001) groups for the recovery time and sucrose versus all other groups for the percent change in heart rate at 3 minutes. The infant body coding system showed that babies in the sucrose group had significantly lower scores followed by the breast-fed and breast milk groups (P = .0001). Our study revealed that 25% sucrose is superior to breast-feeding in pain relief, which is reflected mainly in crying time and behavioral variables. The behavioral effects of breast-feeding did not provide any additional benefit. (C) 2001 by the American Pain Society.
Keywords: newborn; pain; RELIEVING PROCEDURAL PAIN; HUMAN NEWBORNS; 10-DAY-OLD RATS; INDUCED ANALGESIA; HYPOALGESIA; MEDIATION; EFFICACY; INFANTS; TRIAL